Cross Infection Control Awareness During 5th Wave of Covid 19 Pandemic, Omicron Variant Amongst the Dental Health Care Professionals of Government Sector University in Karachi, Pakistan - Hina Shah, Sadaf Talha, Syed Mohsin Ahmed Rizvi, Marium Irshad, Nazish Nisar, Aruba Fatima, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective of this study is to evaluate the awareness of cross-infection control measures followed by DHCPs during the 5th wave of Covid-19 pandemic, Omicron variant in a government sector university of Karachi, Pakistan. Method: A Cross-sectional study was conducted from June till September 2022 at Sindh Institute of Oral Health Science during the 5th wave of Covid 19 pandemic, Omicron variant. Data was collected from 153 DHCPs from government sector university using a self-administered questionnaire, comprising of 20 closed ended question to assess the awareness and practice of cross infection protocols by DHCPs. Results: 98.7% of the participants were vaccinated against Covid 19. 96% of the participants used surgical gowns, face shields, and face masks as part of PPE during examining patients and while performing procedure. After treatment 99.3% of participants washed hands with hand wash, soap or used antiseptic solution. 77.1% of participants asked for Covid 19 test report and 68.6% of participants asked for proof of vaccination against covid 19 before treating patients. 96.1% of participants recommended disinfection of dental unit after every patient. 98% of participants changed glove after every patient. 88.2% of the participants said they would carry all elective and emergency procedures. Conclusion: The results of this study show that DHCPs practicing at government sector university have adequate knowledge regarding prevention of cross infection protocols and their importance to limit spread of infections. But their practice of prevention of cross infection during Covid 19 pandemic is not ideal as percentage of DHCPs requiring proof of vaccination or negative reports for Covid 19 were rather low and the percentage of DHCPs willing to carry elective procedures along with emergency ones was rather high. Keywords: Covid 19 pandemic, Omicron virus, cross infection control protocols, omicron